A psychosocial analysis of parents' decisions for limiting their young child's screen time: An examination of attitudes, social norms and roles, and control perceptions. Issue 2 (14th October 2015) - Hamilton, Kyra; Spinks, Teagan; White, Katherine M.; Kavanagh, David J.; Walsh, Anne M.
Abstract : Objectives: Preschool‐aged children spend substantial amounts of time engaged in screen‐based activities. As parents have considerable control over their child's health behaviours during the younger years, it is important to understand those influences that guide parents' decisions about their child's screen time behaviours. Design: A prospective design with two waves of data collection, 1 week apart, was adopted. Methods: Parents ( n = 207) completed a Theory of Planned Behaviour (TPB)‐based questionnaire, with the addition of parental role construction (i.e., parents' expectations and beliefs of responsibility for their child's behaviour) and past behaviour. A number of underlying beliefs identified in a prior pilot study were also assessed. Results: The model explained 77% (with past behaviour accounting for 5%) of the variance in intention and 50% (with past behaviour accounting for 3%) of the variance in parental decisions to limit child screen time. Attitude, subjective norms, perceived behavioural control, parental role construction, and past behaviour predicted intentions, and intentions and past behaviour predicted follow‐up behaviour. Underlying screen time beliefs (e.g., increased parental distress, pressure from friends, inconvenience) were also identified as guiding parents' decisions. Conclusion: Results support the TPB and highlight the importance of beliefs for understanding parental decisions for children's screen time behaviours, as well as the addition of parental role construction. This formative research provides necessary depth of understanding of sedentary lifestyle behaviours in young children which can be adopted in future interventions to test the efficacy of the TPB mechanisms in changing parental behaviour for their child's health. Statement of contribution What is already known on this subject? Identifying determinants of child screen time behaviour is vital to the health of young people. Social‐cognitive and parental role constructions are key influences of parental decision‐making. Little is known about the processes guiding parents' decisions to limit their child's screen time. What does this study add? Parental role construction and TPB social‐cognitive factors influence parental decisions. The beliefs of parents for their child's behaviour were identified. A range of beliefs guide parents' decisions for their child's screen time viewing.